The illegal defense of outside defenders against the wingers: New defensive 'techniques'? - Anton Garcia, J. L. (EHF Web Periodical, 2014)
In the recent years have proliferated the illegal actions of the outside defenders against the wings that are trying to shoot at goal. What at the beginning were only sporadic actions of some experienced players which, trying to make difficult the shoot´s action for the wing, "like the Indians in the old American West", masked and hid his decoys and interventions with dissimulations, when verifying that these actions were not sanctioned properly by the referees, over the years and the competitive experience have been increasing the number of players that use this kind of ruses. This is thus in such a way that almost all the junior player´s already understand that "that" is what they must do in these cases and they act as a greater "masters" every time in these circumstances. This fact is taking place with assiduity both in the scope of the masculine handball and in the feminine one. We have even been able to verify how players of lower categories already use in some occasions these "new defensive techniques" that have been universalized with the consent of the referees´ teams. Although also it is certain that some referees apply rigorously and correctly the regulation when these cases happen sanctioning the defender, in my opinion a high percentage of cases the violator is unpunished, especially when the winger, in spite of the infraction committed by the defender, is able to reach his objective and to obtain the goal by shooting. In these cases it is usual that sanction goes to the forgetfulness. This circumstance makes that the number of players who conduct these battles -clearly illegal- it is increased remarkably and more and more this action already we could say that has become "patrimony of the outer defenders´ performance". This fact happens until the point that the question whereupon we opened this article acquires all its sense. The coaches have the right to know that if they must teach these "new techniques" to his players, especially in lower categories, so that when these young players reach at the adult age they can respond to the demands of the game. This article tries to expose the present circumstances and conditions of use, as well as to denounce what in my opinion is a regrettable act that goes against the rules of the game.